Administrative Court as Bureaucratic Reform Catalyst through Administrative Law Enforcement - Deseano, Aurick Adien; Putra, Najwa Hanif Artfian Arrasyid Aulia; Gusthomi, Moh. Imam (Reformasi Hukum, 2025)
The State Administrative Court (PTUN) in Indonesia plays a vital role not only in supervising the legality of government actions but also in promoting bureaucratic reform. This study aims to comprehensively analyze the role of PTUN as a catalyst for bureaucratic reform, the challenges it faces in resolving administrative disputes, and the opportunities it can leverage to enhance public service quality and governance. The research employs a normative juridical method, using analysis of legislation, court decisions, legal literature, and relevant administrative judicial practices. The findings indicate that PTUN functions beyond its judicial capacity by upholding good governance principles, creating legal precedents, and correcting deviant administrative actions. However, the court's effectiveness is hindered by structural and cultural constraints, such as weak regulations on decision enforcement, the absence of supervisory mechanisms, and a low compliance culture. This study concludes that through institutional reform, legal process digitalization, human resource development, and cross-sector collaboration, PTUN can strengthen its role in shaping a more efficient, accountable, and responsive bureaucracy.